2019
DOI: 10.1186/s13643-019-1192-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between depressive symptoms or depression and health outcomes in adults with low back pain with or without radiculopathy: protocol of a systematic review

Abstract: Background: A considerable proportion of adults with low back pain (LBP) suffer from depressive symptoms or depression. Those with depressive symptoms or depression may be at risk of poorer LBP recovery and require more health care. Understanding the role of prognostic factors for LBP is critically important to guide management and health services delivery. Our objective is to conduct a systematic review to assess the association between depressive symptoms or depression and health outcomes in adults with LBP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
5
1
Order By: Relevance
“…The association between depression and cLBP is well-documented and it warrants attention in outpatient physical therapy practice [ 36 , 48 51 ]. Although a meta-analysis by Wong et al found depression 20% of the population with cLBP [ 10 ], we observed depression in 37% of our analytic sample. In the MH-LOW group, nearly 60% of patients had been diagnosed with depression.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The association between depression and cLBP is well-documented and it warrants attention in outpatient physical therapy practice [ 36 , 48 51 ]. Although a meta-analysis by Wong et al found depression 20% of the population with cLBP [ 10 ], we observed depression in 37% of our analytic sample. In the MH-LOW group, nearly 60% of patients had been diagnosed with depression.…”
Section: Discussioncontrasting
confidence: 84%
“…In particular, health-related quality of life (HRQoL)—defined as patient’s self-perceived function and well-being in physical, mental, and social domains of health [ 7 , 8 ]—is often negatively impacted by cLBP [ 8 ]. Previous studies have demonstrated that patients with cLBP are often limited in physical activities [ 9 ], have poor mental health status indicated by anxiety and depression [ 10 ], and participation restrictions in social activities [ 11 ]. HRQoL is one of the core outcome domains recommended for measurement in cLBP population [ 12 ]; yet the extent of HRQoL measurement in physical therapy practice has been mixed [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was a significant increase in depression in the examination of gender-independent BDI scores of patients with low back pain [14]. Moreover, treatments for depressive symptoms and depression in individuals with chronic pain help improve low back pain [15]. In contrast, 50% to 88% of this patient population have sleep problems [16].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the impact of depressive symptoms and depression is important to clinical management of LBP. Patients with subacute LBP and depression will need psychological care in addition to medical or physiotherapy treatment 40–42 …”
Section: Introductionmentioning
confidence: 99%
“…Patients with subacute LBP and depression will need psychological care in addition to medical or physiotherapy treatment. [40][41][42]…”
Section: Introductionmentioning
confidence: 99%